I believe in the historical Jesus - Marshall, I. Howard (Grand Rapids : William B Eerdmans Publishing Company, 1977)
Suggests what is meant by the historical Jesus and how we can study his life.
Bibliography: p. [251]-253.
Keywords: Jesus Christ -- Historicity